Capacity building - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
UNESCO s Biotechnology Action Council reported in 1998 that agricultural biotechnology research was underway in 19 countries in sub-Saharan Africa. Whilst a few laboratories in South Africa, Nigeria, and perhaps Kenya, have the capacity to produce...